Analysis Of Profitability, Capital Structure, And Investment Decisions On Firm Value In Telecommunication Sector Companies Listed On Indonesia Stock Exchange Period 2022-2024 - Mufid Khairi Huwaidi; Yudi Nur Supriadi; Ranila Suciati (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the effects of profitability, capital structure, and investment decisions on firm value. Firm value is an important indicator reflecting investor perceptions of corporate performance and future prospects, particularly in technology-related telecommunication companies. The study uses a quantitative approach with secondary data obtained from the audited financial statements of telecommunication subsector companies listed on the Indonesia Stock Exchange during 2022-2024. The research variables consist of firm value measured by Price to Book Value (PBV), profitability measured by Return on Assets (ROA), capital structure measured by Debt to Equity Ratio (DER), and investment decisions measured by Price Earnings Ratio (PER). The data, comprising 69 firm-year observations, were analyzed using descriptive statistics, multicollinearity testing, simultaneous testing, coefficient of determination, and multiple regression with IBM SPSS Statistics 22. The results show that profitability has a positive and significant effect on firm value, while investment decisions also have a positive and significant effect on firm value. In contrast, capital structure has no significant effect on firm value. Profitability is the most dominant variable affecting firm value. These findings imply that companies should strengthen profitability and improve investment quality to enhance market valuation, while investors may use profitability and investment decision indicators as important considerations in investment analysis.